Switzerland : 2007 Article IV Consultation; Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Switzerland. (IMF Staff Country Reports; Country Report, 2007)
This 2007 Article IV Consultation highlights that Switzerland's economy is performing well. The expansion moved into its fourth year with above average growth and employment, and few signs of inflation. This favorable outcome can be traced to a vibrant external environment, including in global financial markets, strong macroeconomic policies, and key structural reforms in retailing and labor markets. The financial sector is performing well in a favorable cyclical setting. Bank profitability is strong, and financial soundness indicators have improved. Economic growth, employment, financial markets, financial sector, bank profitability, and financial soundness indicators have improved.